(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Contemporary media discourse has evolved into a complex cognitive system that not only transmits information but also actively constructs social reality through linguistic mechanisms. This study explores the interaction between dictum and modus components in proposition predicates, focusing on how global events are variatively interpreted across different media systems. Using the 2026 Middle East conflict as a case study, the research applies a cognitive-discursive framework to analyze linguistic strategies in Western, Middle Eastern, and Uzbek media. The findings demonstrate that while dictum provides referential stability, modus functions as a strategic tool for subjective evaluation and ideological framing. The study further introduces the concept of a monocentric interpretative field, revealing how media texts organize meaning around a central semantic core. These results contribute to media linguistics and cognitive discourse analysis by highlighting the role of language in shaping public perception